2022
DOI: 10.1530/etj-21-0033
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative external beam radiotherapy for locoregional control in iodine refractory differentiated thyroid cancer

Abstract: Background: The role of postoperative external beam radiotherapy (EBRT) in patients with residual iodine refractory differentiated thyroid cancer (IR-DTC) is still inconclusive. The aim of this retrospective study was to evaluate locoregional control (LRC) and overall survival (OS), and potential side effects after postoperative EBRT for both microscopic and macroscopic non-radically resected locally advanced IR-DTC. Methods: Between 1990 and 2016, 49 patients with locally advanced IR-DTC received EBRT for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
4
0
3
Order By: Relevance
“…Our study showed that patients with macroscopic residual disease had a greater rate of cervical progression and a shorter duration of local disease control (62.1 vs. 36.7, p = 0.05). Other studies have also shown a benefit of LR control after cervical EBRT in patients with residual microscopic disease versus gross disease 16–18 . In the study by Groen et al, 18 a comparison of local regional disease incidence at 1.5 and 10 years revealed better cervical disease control in patients with microscopic positive margins than in patients with macroscopic positive margins ( p = 0.016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study showed that patients with macroscopic residual disease had a greater rate of cervical progression and a shorter duration of local disease control (62.1 vs. 36.7, p = 0.05). Other studies have also shown a benefit of LR control after cervical EBRT in patients with residual microscopic disease versus gross disease 16–18 . In the study by Groen et al, 18 a comparison of local regional disease incidence at 1.5 and 10 years revealed better cervical disease control in patients with microscopic positive margins than in patients with macroscopic positive margins ( p = 0.016).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have also shown a benefit of LR control after cervical EBRT in patients with residual microscopic disease versus gross disease. [16][17][18] In the study by Groen et al, 18 a comparison of local regional disease incidence at 1.5 and 10 years revealed better cervical disease control in patients with microscopic positive margins than in patients with macroscopic positive margins (p = 0.016). This finding reinforces the importance of "more complete as possible" surgery, as the rates of local disease control were lower at macroscopic margins even with adjuvant treatment with RAI, systemic therapy and all other modalities usually performed after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Both these studies reported superior loco-regional control with EBRT [12,13]. In another retrospective study by Groen et al, 5 year LRC was 84.3% with EBRT (66 Gy) for microscopic residual disease [14].…”
Section: T4 Disease After Complete Surgical Resection or Microscopic ...mentioning
confidence: 99%
“…Tuy nhiên, các nghiên cứu này chủ yếu thực hiện trên nhóm BN UTTG thể biệt hóa tiến triển tại chỗ, tại vùng, còn ít nghiên cứu về vai trò của xạ trị chiếu ngoài đối với nhóm BN UTTG thể biệt hóa kháng I-131 [5][6][7][8][9][10]. Một vài nghiên cứu đã cho thấy của xạ trị điều biến liều (IMRT) giúp cải thiện kiểm soát tại chỗ, tại vùng cũng như giảm độc tính trong điều trị BN UTTG thể biệt hóa tái phát, di căn [8,10], kháng I-131 [11]…”
Section: đặT Vấn đềunclassified
“…Một số nghiên cứu hồi cứu cũng đã cho thấy hiệu quả của xạ trị chiếu ngoài về cải thiện thời gian sống còn và khả năng kiểm soát tại chỗ, tại vùng trong điều trị UTTG thể biệt hóa, tiến triển kháng I-131 [11]. Nghiên cứu này của chúng tôi đã cho thấy IMRT giúp cải thiện đáng kể khả năng kiểm soát tại chỗ tại vùng (LRC) và thời gian sống còn toàn bộ (OS) ở nhóm BN UTTG thể biệt hóa kháng I-131 tái phát, di căn vùng cổ-ngực.…”
Section: Bàn Luậnunclassified